Strategi Penguatan Apip Bawaslu Dalam Pengawalan Akuntabilitas Dana Hibah Pilkada 2024 - Wildan Husaini, Faik (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2026)
The simultaneous Pilkada in 2024 increased governance risks in grant fund management, requiring effective internal supervision to ensure transparency and accountability. This study analyzes strategies for strengthening the role of the Aparat Pengawasan Intern Pemerintah (APIP) within Badan Pengawas Pemilihan Umum (Bawaslu) in safeguarding the accountability of Pilkada grant funds. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis and analyzed using spiral data analysis and triangulation techniques. The findings indicate that the Inspectorate General of Bawaslu implemented structured and risk-based supervision through audits, reviews, evaluations, monitoring, and consultative assistance throughout the grant fund management cycle. Despite these efforts, supervisory effectiveness remains constrained by extensive coverage, regulatory complexity, and limitations in human resources. Strengthening APIP through capacity building, improved coordination, and refinement of supervisory mechanisms is therefore essential to enhance the accountability and sustainability of Pilkada grant fund management